Relationship between Resources and Value Creation in the Kenyan-owed Mining Enterprises in Kenya - Laiboni, Susan Nyegera; Senaji, Thomas Anyanje; King’oriah, George Kinoti (International Journal of Professional Practice, 2022)
Studies show that countries such as United States of America, Canada, Australia, Chile, Ghana and South Africa use the right machinery and equipment to extract minerals which when sold contribute significantly to the country’s GDP. Kenyan mining industry contributed Ksh.15023 million only to the GDP in the second quarter of 2020. Therefore, it was important to establish whether Kenyan owned mining enterprises have adequate resources. The objective of this study was to establish whether resources have a relationship with value creation. This study was a cross sectional survey. A questionnaire was used to collect data from Kenyan owned mining enterprises, where both semi-structured and open-ended questions were used. A quantitative approach was employed in data analysis. Results of the research demonstrated that there was correlation between resources and value creation. ANOVA results show that resources and value creation association were statistically significant. However, Kenyan owned enterprises do not have adequate resources. This study found out that most of the Kenyan owned mining enterprises do not have adequate resources to facilitate value creation processes. These resources are crucial in mining industry because finances are used to acquire all other resources, such as machines and equipment resources that are used to extract minerals throughout the value chain process in the mining industry. Future studies can be undertaken to establish whether other specific types of mining-related enterprises have resources to facilitate mining process.